HUBUNGAN PENGETAHUAN DAN SIKAP ANAK KELAS V TERHADAP TERJADINYA KARIES GIGI DI SD NEGERI 131 PALEMBANG - Hardika, Bangun Dwi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Health is the most important thing in people life, physically and mentally. Besides body?s health in general teeth and mouth health also must get special attention, because teeth and mouth health affects body?s health. Dental caries is a pathological process that occurs because of the interaction of factors inside and outside factors such as behavioral factors, knowledge and attitudes toward maintenance of teeth and mouth. The research aimed to understand the relationship between knowledge and attitude of grade V students of 131 elementary school Palembang toward the teeth caries. The method used in this research is analitical method by using cross sectional design, taking samples technique by using total population way and the samples are 167 student of grade V. From The result of this study it was know that, 33.5% of children who have a low knowledge, 43.1% of children have negative attitudes and 59.3% of children experienced dental caries. From Chi square test results showed no relationship between knowledge of children with dental caries with p value of 0.036; there is a correlation between the attitudes of children with dental ceries with p value, 0.000. In order to decrease the number of teeth caries among students, it is hoped that school make a school teeth health unit (UKGS) and some mediators and teachers need to make a teeth health socialization so that the students can get more knowledge about teeth and mout health. Key word: Knowledge, Attitude, and Teeth Caries